Mittag-Leffler Filter and Its Application in Bio-signals Processing - Petras, Ivo (Signal Processing Algorithms, Architectures, Arrangements, and Applications Conference proceedings, 2024)
This contribution introduces a novel variant of the well-known low-pass Gaussian filter, the Mittag-Leffler filter, applicable in 1D and 2D contexts. This new filter incorporates a Mittag-Leffler function within its probability density function. It features three tunable parameters that adjust the curve shape and the filter's forgetting factor. Illustrative examples involving two real ECG signals (one male and one female) and a real MRI image (female) highlight the main advantages of the proposed filter in comparison to the traditional Gaussian filtering (denoising) technique. Implementation details and the Matlab functions for the proposed 1D and 2D filters are provided too.